Oral History Program Interview: Elbert Mendenhall - Mendenhall, Elbert
Mendenhall was born on March 10, 1902 in Ponca, Dixon County, Nebraska. He and his family came out to Los Angeles in November of 1936. Mendenhall's interview presents a perspective of a Nebraskan migrant; in particular, the effects of President Roosevelt's program that destroyed livestock and crops, how unions made it difficult to find work, and strikes' disruptive nature for families trying to earn wages. He also includes his wife's problems with employers replacing her with male employees.